The detection of mixed tuberculosis infections using culture filtrate and resuscitation promoting factor deficient filtrate - Chengalroyen, Melissa D.; Beukes, Germar M.; Otwombe, Kennedy; Gordhan, Bhavna G.; Martinson, Neil; Kana, Bavesh (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculosis (TB) infected individuals harbor a heterogenous population of differentially culturable tubercle bacilli (DCTB). Herein, we describe how DCTB assays using culture filtrate either containing or deficient in resuscitation promoting factors can uncover mixed infections. We demonstrate that Mycobacterium tuberculosis (Mtb) strain genotypes can be separated in DCTB assays based on their selective requirement for growth stimulatory factors. Beijing mixed infections appear to be associated with a higher bacterial load and reduced reliance on growth stimulatory factors. These data have important implications for identifying mixed infections and hetero-resistance, which in turn can affect selection of treatment regimen and establishment of transmission links.